SGLT2 inhibition attenuates diabetic tubulopathy by suppressing SGK1-mediated pyroptosis - Shi, Xu; Zou, Wei; Li, Xuehong; Liu, Sirui; Hu, Tiantian; Li, Qiong; Zhang, Ting; Chen, Lei; Wu, Sumin; Wang, Cheng; Jin, Yongjie (Frontiers in Endocrinology, 2025)
BackgroundDiabetic tubulopathy is increasingly recognized as a pivotal contributor to diabetic kidney disease (DKD) progression. Excessive pyroptosis of renal tubular epithelial cells exacerbates inflammation and tissue injury. Although sodium-glucose cotransporter 2 (SGLT2) inhibitors confer renal protection, their mechanistic linkage to pyroptosis remains unclear.MethodsRenal biopsies from DKD patients, STZ-induced diabetic mice, and high glucose (HG)-stimulated HK-2 cells were analyzed. Pyroptosis markers and SGK1 signaling were assessed following SGLT2 knockdown, overexpression, or treatment with SGLT2 inhibitor empagliflozin (EMPA) and the SGK1 inhibitor EMD638683 (EMD).ResultsSGLT2 and Gasdermin D N-terminal domain (GSDMD-N) were upregulated in DKD kidneys and correlated with tubular injury and renal dysfunction. EMPA reduced pyroptosis marker expression, tubular injury, and fibrosis in diabetic mice. In vitro, HG induced SGLT2 upregulation, SGK1 activation, and pyroptosis in HK-2 cells, which were reversed by EMPA. SGLT2 overexpression increased SGK1 and pyroptosis even under normoglycemia, while SGK1 inhibition suppressed HG-induced pyroptosis and NF-κB activation.ConclusionSGLT2 promotes diabetic tubular injury through SGK1-mediated pyroptosis. Inhibition of the SGLT2/SGK1 axis alleviates pyroptosis and offers a potential therapeutic strategy for DKD.